2017
DOI: 10.1007/s40258-017-0342-x
|View full text |Cite
|
Sign up to set email alerts
|

Health Expenditure and All-Cause Mortality in the ‘Galaxy’ of Italian Regional Healthcare Systems: A 15-Year Panel Data Analysis

Abstract: The results highlight the importance of medical services and goods provided directly by public services (i.e. hospital-based general and specialized wards and offices, emergency departments, etc.). DPS represents the driving force of the system and should be considered a determinant of the health of the Italian population. Our results suggest that the context and financing methods of a healthcare system should be carefully analysed before linear cuts are made or resources are reallocated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 32 publications
1
29
0
Order By: Relevance
“…The panel data analysis described the association between health spending and mortality and showed that DPS is the only spending item significantly related with mortality in all models considered. This result is consistent with our prior findings [ 39 ]. Our models confirm that DPS is the financial driving force of the publicly funded Italian health system, and a potential determinant of the Italian population health status.…”
Section: Discussionsupporting
confidence: 94%
“…The panel data analysis described the association between health spending and mortality and showed that DPS is the only spending item significantly related with mortality in all models considered. This result is consistent with our prior findings [ 39 ]. Our models confirm that DPS is the financial driving force of the publicly funded Italian health system, and a potential determinant of the Italian population health status.…”
Section: Discussionsupporting
confidence: 94%
“…by AEs, general and specialized hospital wards, and so on. In our previous work [2], we identified DPS as the major driving force of the INHS, the one most closely related to overall mortality rate, one of the most important outcome measures for evaluating a health system's performance. However, this spending item adjusted by inflation saw a constant reduction in recent years together with an even stronger reduction in the spending for primary care (Fig.…”
Section: To the Editormentioning
confidence: 99%
“…On the other hand, Nkemgha et al (2020) identified the positive and statistically significant influence of private health expenditure but no significant impact of public health expenditure on life expectancy in Cameroon during 1980-2014. Similarly, van den Heuvel and Olaroiu (2017) declared that public health expenditure is not a key determinant of life expectancy while conducting a study in 31 European countries for the data period of 2014-2014. Many other researchers pointed out the positive role of both public and private health care expenditure on health status.…”
Section: Health Status -Health Expenditure Nexusmentioning
confidence: 99%
“…The major contributions of this study are: (i) this is the first study in the literature, to the best of our understanding, that investigates the effects of public and private health expenditures, energy consumption, carbon emissions, economic growth, and sanitation facilities on health status in the context of SAARC-BIMSTEC regions; (ii) this work employs the latest available and inclusive data covering the period of 16 years (2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012)(2013)(2014)(2015)(2016)(2017); (iii) the results are attained by employing various erudite econometric tools e.g.…”
Section: Introductionmentioning
confidence: 99%